The importance of the otorhinolaryngologic evaluation in mucopolysaccharidosis patients - Bicalho, Cibele Gomes; Rezende, Morena Morais; Nogueira, Ana Maria Carrilho Moinhos; Paulon, Roberta Melo Calvoso; Acosta, Angelina Xavier (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Mucopolysaccharidosis (MPS) is a group of rare diseases caused by the deficit of lysosomal enzymes, causing an accumulation of glycosaminoglycans (GAG) in organs and tissues responsible for the multi-systemic clinical, chronic and progressive status.Objective: Describe the profile of the otorhinolaryngologic clinical evaluation in patients submitted to Enzyme Replacement Therapy (ERT) and suggest an algorithm to otorhinolaryngolgically follow up with these patients.Method: A study with a number of cases was performed, including 21 patients having MPS I, II and VI.Results: The most common otorhinolaryngological complaints were nasal obstruction, snore, and mouth-breathing. Apnea was reported in 31% of the cases. In the physical examination, macroglossia was the main alteration (41%) of oral pharyngoscopy. At otoscopy, the retraction of the tympanic membrane was found in 33% and hearing loss was found in 45%.Conclusion: It is important to evaluate the complaints, physical examination and the impact of alterations associated with MPS-produced breathing and hearing, for purposes of better following up with these patients and preventing consequential chronic alterations such as hearing loss, sleep disorder, and mouth breathing, thus, enhancing these patients' quality of life.
Keywords: glycosaminoglycans; mucopolysaccharidosis; otolaryngology